Evaluation of User Experience for the OVO Application using the User Experience Questionnaire Method (UEQ) - Fariha, Umi; Saputra, Eki; Hamzah, Muhammad Lutfi; Fronita, Mona (Sistemasi: Jurnal Sistem Informasi, 2024)
Along with advances in digital technology, the ease of carrying out payment transaction processes via digital wallet applications is increasing. OVO is one of the leading digital wallet applications in Indonesia. However, there are several users who complain and report problems such as difficulties in upgrading, login problems, transaction failures, and applications that respond slowly. These reviews can be seen through the comments column in the OVO application on Google Playstore. Application representation can influence user perceptions of an application. This research aims to assess the user experience of the OVO application using the User Experience Questionnaire (UEQ) method, which involves six aspects of assessment: attractiveness, clarity, efficiency, stimulation and innovation. The research results obtained show that the overall user assessment of the evaluation that has been carried out on the OVO application is positive. This research is expected to be able to provide important insights and information regarding user satisfaction with digital wallet applications. Apart from that, it is also hoped that this research can become a reference for subsequent research and further development related to the OVO application, with the aim of improving the user experience.